Variation in SiMn Composite Composition Using Modified Polydimethylsiloxanes (PDMS) on Corrosion Properties and Contact Angles - Eka Cahya Muliawati; Dwi Lulu Laurantini (CV. Get Press Indonesia, 2025)
Corrosion is one of the main challenges faced by advanced industries today because it can cause major losses in terms of safety and economy. One of the common protection methods used to reduce the impact of corrosion is polymer-based coating, which can provide hydrophobic properties on the substrate surface. This study aims to examine the effect of variations in the composition of silica-manganese (SiMn) composites reinforced with polydimethylsiloxane (PDMS) on hydrophobic properties, corrosion resistance, and contact angles. The coating method used is spin coating, with the substrate being a mixture of hard and strong silica and manganese which has corrosion-resistant properties. The SiMn compositions varied were 40%:60%, 50%:50%, and 60%:40%. This study is experimental, using tools such as HEM-3D, XRD, SEM, and FTIR. The coating process was carried out by mixing 2.5 grams of PDMS with silica and manganese powders with a total weight of 1 gram, according to the composition variations. The contact angle test was conducted using a DSLR camera, while the corrosion resistance test was conducted using the immersion method in sulfuric acid with the mass loss method. The results showed that variations in composition affected the contact angle and corrosion resistance of the SiMn-PDMS layer. The composition of 0.6 grams of silica and 0.4 grams of manganese produced the highest contact angle of 120.66⁰, indicating higher hydrophobic properties. Conversely, the composition of 0.4 grams of silica and 0.6 grams of manganese showed the lowest corrosion rate, which was 1.57 cm/hour.